Harsh Parenting and Internet Addiction: The Chain Mediating Effect of Emotional Regulation Difficulties and Maladaptive Cognitions. - Wang, Huan; Liu, Huimin; Zhou, Lulu; Bi, Xinyue; Tao, Jingting; Jiang, Yuan; Zhang, Rong; Musetti, Alessandro (Perspectives in Psychiatric Care, 2024)
Adolescents who have experienced harsh parenting face an increased risk of developing Internet addiction (IA) later in life. Few studies have examined the underlying mechanisms between harsh parenting and IA. This study explores the relationship between harsh parenting and IA, focusing on associations with emotional regulation difficulties and maladaptive cognitions. The study group consisted of 925 adolescents (Mage = 16.16, SDage = 0.72; 48.54% girls) who were recruited to complete a survey measuring the variables of harsh parenting, difficulties in emotional regulation, maladaptive cognitions, and IA. After accounting for age and gender, it was found that harsh parenting is directly associated with adolescents' IA (β = 0.07, p < 0.01). The chain mediating effect of emotional regulation difficulties and maladaptive cognitions was 0.08 (95% CI [0.06, 0.10]), which implies that a chain mediation was identified between harsh parenting and IA through the intermediary factors of emotional regulation difficulties and maladaptive cognitions. The findings suggest that addressing the emotional regulation difficulties and maladaptive cognitions could be important aspects to consider in interventions and prevention efforts aimed at reducing adolescent IA.